2020
DOI: 10.1002/adbi.202000161
|View full text |Cite
|
Sign up to set email alerts
|

Early Committed Clockwise Cell Chirality Upregulates Adipogenic Differentiation of Mesenchymal Stem Cells

Abstract: determine the LR asymmetry in morphogenesis. [2] For example, chirality has been found in Xenopus egg cortex before fertilization, [1] and can be passed down to more differentiated cells that establish LR body axis of animal body plan, [7] organ distribution, [8-10] and epithelial movement that leads to axial torsion and overall handedness of hindgut. [11,12] For specialized adult cells derived from somatic tissue, footprints of cell chirality can still be seen by their ability of generating cellular torque, [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…3a). Using automated image processing to analyze the tilting angle of actin lament with respect to the radial axis of each cell 23 , a ACW bias was found (Fig. 3b), which is consistent with previous ndings 22 and the nucleus rotation mentioned above.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…3a). Using automated image processing to analyze the tilting angle of actin lament with respect to the radial axis of each cell 23 , a ACW bias was found (Fig. 3b), which is consistent with previous ndings 22 and the nucleus rotation mentioned above.…”
Section: Resultssupporting
confidence: 90%
“…We next explored the potential regulation of cell differentiation by adjusting the cell chirality. Previously we have shown that hMSCs would early committed to a CW chirality with adipogenic induction, which may possibly serve as the mechanical precursor to engage the cell phenotype toward the adipogenic lineage 23 . To explore whether the expression of mDia2 can guide the lineage speci cation, we applied mDia2 silencing to hMSCs (24 hours of transfection and 12 hours of recovery in growth media) before adipogenic and osteogenic dual induction and count the lineage speci cation by Oil Red O staining (for adipocytes) and Fast Blue staining (for osteoblasts) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Geometric chirality modulates the enhancement or cancellation of the intrinsic chirality of the cytoskeleton, thereby altering cytoskeleton contractility to mediate asymmetric cell fates and significantly affect the osteogenic differentiation behavior of cells. 20 That is, the intracellular actin organization mechanism is the physical mechanism in which the cells are modulated by material chirality bias. 21…”
Section: Introductionmentioning
confidence: 99%